This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
You can easily find the antiderivate of lo g x by using the integration by parts. ∫ lo g x = x lo g x − x + C
Taking the limits of integration: 0 ∫ 1 lo g x = x lo g x − x ∣ 0 , 1 = − 1 − lim x − > 0 x lo g x
Soving the limit by the L'hopital's rule: − 1 − lim x − > 0 x lo g x = − 1 − lim x − > 0 x 1 lo g x = − 1 − lim x − > 0 x − x 2 = − 1